2013 Global food policy report - International Food Policy Research Institute (International Food Policy Research Institute, 2014)
This 2013 Global Food Policy Report is the third in an annual series that provides an in-depth look at major food policy developments and events. Initiated in response to resurgent interest in food and nutrition security, the series offers a yearly overview of the food policy developments that have contributed to or hindered progress in achieving food and nutrition security. It reviews what happened in food policy and why, examines key challenges and opportunities, shares new evidence and knowledge, and highlights emerging issues.